Preliminary Results Indicate That Inactivated Vaccine against Paratuberculosis Could Modify the Course of Experimental Mycobacterium bovis Infection in Calves - Serrano, Miriam; Elguezabal, Natalia; Sevilla, Iker A.; Geijo, María V.; Molina, Elena; Juste, Ramón A.; Garrido, Joseba M. (Frontiers in Veterinary Science, 2017)
Although paratuberculosis (PTB) vaccination has been recognized as an effective tool to control the disease, its use has been limited in countries undergoing bovine tuberculosis (bTB) eradication programs because of its interference with the diagnostic techniques. Due to this restraint, little is known about the effect of vaccinating against PTB on the progression of bTB infection. To assess this topic, an experimental infection was carried out including three groups of five calves each: non-vaccinated infected with M. bovis (NVI), vaccinated against PTB infected with M. bovis (VI) and vaccinated against PTB non-infected (VNI). The level of infection attending to pathological and bacteriological parameters was evaluated at necropsy in collected tissue samples. Infection was confirmed in all challenged animals being the lung and thoracic regions most affected for all studied parameters. The VI group presented 15.62% less gross lesions in the thoracic region than the NVI, although no significant differences were found. Only one vaccinated animal presented gross lesions in the lung, compared to three non-vaccinated calves. NVI animals showed an average of 1.8 lung lobes with gross lesions whereas in the vaccinated group the average number of affected lobes was 0.2, representing an 89% reduction. Significant differences were not found, although a tendency was observed (p=0.126). Pathological and culture scores showed the same tendency. Vaccination induced a 71.42% and 60% reduction in lesion and culture scores in the lung as well as a 23.75% and 26.66% decline respectively in the thoracic region. The VI group showed lower positivity in the rest of the areas for all measured criteria except for the head. In order to reinforce our results further research on a larger sample size is needed but, the results from this study suggest that PTB vaccination could confer certain degree of protection against bTB infection, supporting the view that PTB vaccination could increase resistance to the main mycobacterioses that affect animals.